Prevalence of reproductive tract infections among ever married women of age 18 to 49 years in a rural area of Cuddalore district, Tamil Nadu - P., Sahana; I. K., Annie; Felix A., John William (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Reproductive tract infections (RTIs) affect not only women’s health but also has its implications on child health, family and socioeconomic development of the community. Unless the symptoms become alarming, women with RTI don’t seek health care. If untreated or inadequately treated RTI can lead to complications causing morbidity and mortality. So, this study focused to find out the prevalence of RTI among ever married women and its association between RTI and sociodemographic variables in a rural area. Methods: This community based cross sectional study was conducted from September 2021 to March 2022 among ever married women of 18 to 49 years in a rural area, Parangipettai, Cuddalore district, Tamil Nadu. A total of 320 women were interviewed by a house-to-house survey. Structured pretested questionnaire was used to collect data on symptoms of RTI, sociodemographic and obstetric variables. Results: Out of 320 study participants, the prevalence of RTI was found to be 23.8% (n=76). The most common symptoms reported was vaginal discharge 14.37% followed by lower abdominal pain 13.75%. This study showed that RTI was significantly associated with age of women (p=0.006) and previous history of abortion (p=0.023). Conclusions: In spite of various health programs in place, the prevalence of RTI was as high as 23.8% in this study. This implies sensitizing rural women about RTI at regular intervals is necessary for reducing the burden and preventing the complications of RTI.